PERILAKU PROFESIONAL TENAGA KESEHATAN DAERAH PESISIR PADA PELAYANAN KESEHATAN PRIMER PUSKESMAS SINABOI KABUPTEN ROKAN HLIR TAHUN 2014 - Bhelprinosa Arwen; WIWIT ADE FIDIAWATI; Dedi Afandi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Indonesia is a developing country that continues its effort to actualizing the community prosperity. The effort of enhancing the primary health care service, especially in the coastal area is a priority to health development because it can cover all the remote areas. Health care success depends on the behavior of its health-care workers. Workers with professional behavior are the main elements in actualizing an effort to an optimal health. Professional behavior is very important to build a trust in a middle of society that becomes critical with the quality of health care performance in health service. The aim of this research is to discover the professional behavior of Sinaboi community health care in Rokan Hilir Regency based on six professionalism elements. This study is using an exploration method with quantitative approaches on seven health workers in Sinaboi community health care that was chosen with the snowball sampling method. Data were collected by using interview method recorded with an audio recorder. The result shows that all informants possess altruism, accountability, duty and respect for others and some of the informants possess excellence. In general, some of the health care workers in Sinaboi community health care have possessed a professional behavior in performing their proffesion, especially in providing service for patients.Key word : professional behavior, health-care workers